2018
DOI: 10.1021/acs.jpcb.8b09777
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Surfactant Flooding Driven Oil-Detachment in Nano-Silica Channels

Abstract: Recovery of crude oil in rock nanopores plays an important role in the petroleum industry. In this work, we carried out molecular dynamics (MD) simulations to study the process of ionic surfactant solution driven oil-detachment in model silica (SiO 2 ) nanochannels. Our MD simulation results revealed that the oil-detachment induced by the ionic surfactant flooding can be described by a three-stage process including the formation and delivery of surfactant micelles, the surfactant micelle disintegration-spread … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 54 publications
2
19
0
1
Order By: Relevance
“…SongKaoping Group [34] in China was the first to describe the mechanism of improving the oil displacement efficiency of polymer by using the basic principles of molecular dynamics, and compared with the molecular force of water flooding, the viscoelasticity of polymer solution is the macroscopic manifestation of the collision force and friction force between polymer molecules and crude molecules, which can enhance the oil detachment efficiency. Fan et al [41] explored the mechanism of viscoelastic polymers to enhance oil recovery through MD simulations, and visualized the dynamic process of displacement of oil droplets trapped in nanopores from dead end. The research shows that the key factor for polymer flooding to perform well in recovery is the unique elastic properties of polymer molecules.…”
Section: Analysis Of Polymer Floodin Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…SongKaoping Group [34] in China was the first to describe the mechanism of improving the oil displacement efficiency of polymer by using the basic principles of molecular dynamics, and compared with the molecular force of water flooding, the viscoelasticity of polymer solution is the macroscopic manifestation of the collision force and friction force between polymer molecules and crude molecules, which can enhance the oil detachment efficiency. Fan et al [41] explored the mechanism of viscoelastic polymers to enhance oil recovery through MD simulations, and visualized the dynamic process of displacement of oil droplets trapped in nanopores from dead end. The research shows that the key factor for polymer flooding to perform well in recovery is the unique elastic properties of polymer molecules.…”
Section: Analysis Of Polymer Floodin Mechanismmentioning
confidence: 99%
“…Tang et al [41] utilized MD simulation to explore the process of ionic surfactant solution driven oil dispalcement in SiO 2 nanochannels model (see Figure 5), which can be illustrated by a three-stage process, including the formation and delivery of surfactant micelles, the disintegration-spread and migration of surfactant micelles on the surface of oil aggregate, and the deformation-to-detachment of oil molecular aggregate; Under the action of water flow, the surfactant molecules migrate to the rear bottom of the oil aggregate, allowing the water molecules to occupy the surface sites of the oil molecules and cause the oil molecules to detach; The SDBS exhibited a better oil displacement efficiency than DTAB (consistent with the results of literature [40]), this is because the -SO -3 group in SDBS is more attractive to water molecules, which leads to faster migration of SDBS on the surface of oil aggregate, thus obtaining higher deformation-detachment speed of oil molecules, and the simulation results are useful to understand the interaction between surfactant solution and crude oil and provide some fresh understanding for the process of surfactant flooding to enhance oil recovery. Figure.…”
Section: Application Of Molecular Simulation In Surfactant Floodingmentioning
confidence: 99%
“…Tang et al 51 studied a process of oil recovery during surfactant flooding in nanoporous quartzes using two different types of surfactants, including cationic, dodecyl tri-methyl-ammonium bromide, and anionic, Dodecyl Benzene Sulfonate (SDBS). According to their results they gained from MD simulation, the headgroup's tendency to form hydrogen bonds with water as an anionic surfactant was higher than the cationic one.…”
Section: Introductionmentioning
confidence: 99%
“…The simulated results showed that the main mechanism of surfactants enhanced oil recovery [ 28 ] is that surfactants can reduce the oil/water interfacial tension and change the interfacial property of heavy oil and water phase [ 29 ]. The simulation results of Tang et al [ 30 ] indicated a three-stage process of surfactant flooding driven oil-detachment, including the initial formation of surfactant micelles and delivery, the disintegration-spread and migration of surfactant molecules on the oil aggregate. Bhattacharjee et al studied the aggregates of asphaltenes in water/organic solvent systems [ 31 ].…”
Section: Introductionmentioning
confidence: 99%